RECOMMENDATIONS FOR TEACHING BORROWED WORD IN MODERN CHINESE (Journal of Foreign Language Studies, 2024)
The borrowed word is a kind of word changing from this language to another language which is being used, so it is also called the loan. The appearance and existence of the loanwords is an inevitable phenomenon due to the interaction and influence between languages and different cultures. Therefore, except for some languages isolated by the outside world, the loanwords exist in almost languages in the world. In modern Chinese, the loanwords exist in large numbers. And also appeared a number of problems to both teachers and learners when using this type of word. In terms of comparative linguistics, this research has shown that being an integral part of modern Chinese vocabulary, the majority of the loanwords has achieved the unity under six major trends with a relatively low rate of uniformed foreign words. The study of unified trends of how to use loanwords in modern Chinese is a basis through which we can give some recommendations about the teaching methods of this linguistic phenomenon, contributing to language teaching in general and Chinese in particular.
Keywords: loanwords; modern Chinese; unified trend; notices